Switched Antenna Array for Maritime Communications - Diogo André Durães Moreira (2018)
In this dissertation work, different antenna topologies are evaluated to find the best design capable of overcoming the difficulties of communications at high seas. The impact of multiple design variables is studied, and their effects explained resorting to theoretical principles. Furthermore, a switching matrix of eight sectors is also designed, so the antenna beam direction can be automatically reconfigured with the movement of the vessel. The antenna and both the feeding and switching networks were designed and validated resorting to Finite Element Method in HFSS and the Method of Moments in ADS, respectively. The final antenna element experimental results show a fractional impedance bandwidth of 22.3 %, an isolation between inputs above 45 dB and a gain of 7.5 dBi at the centre frequency of 5.15 GHz. Through simulation, it is shown that when the unit element is connected to the switching network, the fractional bandwidth remains unchanged. Finally, the experimental measurements were compared with the simulated results of the unit cell and the entire system.